Removing dubious feedback from mobile wireless ad hoc peer-to-peer systems. (29th July 2011) - Han, Jinsong; Zhao, Jizhong; Xi, Min; Sun, Xingming
In MObile wireless ad hoc Peer-to-Peer NETworks (MOPNETs), Reputation-based Trust Management (RTM) is essential for peers to choose reliable resources and trusted cooperators. However, outliers or misbehaving peers often overpraise their friends while denigrating strange peers. As a result, it is challenging to guarantee the validation and accuracy of RTM In this paper, we propose an extensive RTM scheme, TruthMOP. TruthMOP encourages peers to provide honest feedback by involving the quality of their evaluations of others into computing reputations. The simulation results show that TruthMOP can effectively mitigate the impact of dubious feedback in MOPNETs.